Hacking Web Intelligence. (August 2015) - Unknown
Abstract : The general population's image of the hacker – and one shared by many script-kiddies and would-be 'leet' fantasists – is of someone with arcane knowledge bordering on black magic that is put to use cracking into systems of mind-boggling complexity.